2023
DOI: 10.3390/polym15122598
|View full text |Cite
|
Sign up to set email alerts
|

Development of Light-Polymerized Dental Composite Resin Reinforced with Electrospun Polyamide Layers

Aleksandra Maletin,
Ivan Ristić,
Aleksandra Nešić
et al.

Abstract: As the mechanical properties of resin-based dental composite materials are highly relevant in clinical practice, diverse strategies for their potential enhancement have been proposed in the extant literature, aiming to facilitate their reliable use in dental medicine. In this context, the focus is primarily given to the mechanical properties with the greatest influence on clinical success, i.e., the longevity of the filling in the patient’s mouth and its ability to withstand very strong masticatory forces. Gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This innovative approach led to substantial improvements, increasing the bending strength, elastic modulus and work of rupture by more than 20%. 10 In subsequent studies, more ESNs were introduced to reinforce dental resins, including polyacrylonitrile (PAN), 71 polyamide (PA), 72 PVA, 73 and multi-walled carbon nanotubes (MWCNT). 74 Maletin et al interspersed light-cure dental composite resins with PA nanofibers and investigated the mechanical properties of the resulting hybrid resins.…”
Section: Esns Application In Caries Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This innovative approach led to substantial improvements, increasing the bending strength, elastic modulus and work of rupture by more than 20%. 10 In subsequent studies, more ESNs were introduced to reinforce dental resins, including polyacrylonitrile (PAN), 71 polyamide (PA), 72 PVA, 73 and multi-walled carbon nanotubes (MWCNT). 74 Maletin et al interspersed light-cure dental composite resins with PA nanofibers and investigated the mechanical properties of the resulting hybrid resins.…”
Section: Esns Application In Caries Lesionsmentioning
confidence: 99%
“…The results showed that the inclusion of a 16 μm-thick PA nanolayer enabled the dental composite resin to withstand a load of 3.2 MPa without affecting the polymerization reaction process, and immersing the resin in saline solution may further provide a more compact composite material structure. 72…”
Section: Esns Application In Caries Lesionsmentioning
confidence: 99%
See 1 more Smart Citation